Persepsi Jurnalis Tentang Pemanfaatan Artificial Intelligence (AI) Dalam Pembuatan Berita: Studi Kasus Jurnalis Lokal Surakarta - Sabila Soraya Dewi; Sri Hastjarjo (Universitas Sebelas Maret (UNS), 2024)
Over the past few decades, there has been a shift in the media industry, where conventional media such as newspapers and television have started to lose their popularity. This change has been accelerated by the emergence of Artificial Intelligence (AI) which is now being used in journalism. The use of AI raises the question of how local journalists respond to this technology: do they see AI as a tool that supports their work, or do they feel threatened by its presence? Using the Technology Acceptance Model (TAM) theory, this research seeks to explore local journalists' perceptions of AI tools in news processing. The research was conducted using a qualitative method using a case study approach, where data was obtained by conducting interviews with local journalists in Surakarta. The results found include first, AI tools improve journalists' work efficiency by speeding up typing, data search, editing, audio processing, and research, as well as monitoring online news trends. Second, although some AI tools are easy to use, mastering them still takes time and training, especially because AI sometimes makes work more difficult. Third, it is perceived that AI is not yet able to fully maintain the Journalistic Code of Ethics and press regulations need to be updated. However, it is perceived that AI will not violate ethics if humans are in full control.